Entrepreneurship and small business development in post-socialist economies [electronic resource] - Smallbone, David; Welter, Friederike (New York : Routledge, 2009)
Examining entrepreneurship and small business in Russia and the key countries of Eastern Europe, this book shows how small businesses have developed, and discusses how market reforms and a market mentality have been taken up by ordinary people in the real everyday economy.
1. Introduction. Part A. Setting The Scene. -- 2. Entrepreneurship, Sme Development And The Transformation Process. -- 3. Entrepreneurship In Transition Economies: A Conceptual Review . Part B. Entrepreneurship And Small Business Development In Former Soviet Republics. -- 4 Employment In New And Small Firms: The Example Of The Russian Federation. -- 5. Coping With Adversity:The Case Of Belarus. -- 6. Innovation And Entrepreneurship Under Transition Conditions: The Example Of The Ukraine. Part C. Entrepreneurship And Small Business Development In Central And Eastern Europe. -- 7. Poland: Eu Accession And Entrepreneurship Development. -- 8. From The Former Soviet Union To Membership Of The European Union: The Case Of Estonia
Description based on print version record
Includes bibliographical references and index
Keywords: Entrepreneurship -- Case studies; Post-communism -- Economic aspects -- Case studies; Small business -- Case studies